Autistic people's perspectives on stereotypes: An interpretative phenomenological analysis. (April 2019) - Treweek, Caroline; Wood, Chantelle; Martin, Jilly; Freeth, Megan
Autism stereotypes can often portray autistic people in a negative way. However, few studies have looked at how autistic people think they are perceived by others, and none have specifically asked autistic people what they think the autistic stereotypes are. Semi-structured interviews with 12 autistic adults (aged between 20 and 63 years) were conducted. Using interpretative phenomenological analysis, three main themes emerged from the data. These were as follows: (1) the primary stereotype is that autistic people are 'weird'; (2) autistic stereotypes have negative effects and consequences; and (3) autistic people are heterogeneous. This study makes an important and novel contribution to understanding the experience of being autistic by exploring how autistic people feel they are perceived by others and identifying some of the ways in which negative stereotypes are believed to have negative consequences for autistic people.